2020
DOI: 10.34172/ps.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons Degradation by Aquatic Bacteria Isolated from Khazar Sea, the World’s Largest Lake

Abstract: Background: Aquatic microorganisms have an important role in the bioremediation of environmental pollutants. Polycyclic Aromatic Hydrocarbons (PAHs) are described as dangerous pollutants that can bind covalently to the nucleic acids, causing mutations. Therefore, they have carcinogenic and toxic properties. Also, are involved in diseases such as asthma, lung dysfunction, and chronic bronchitis. This study aimed to isolate and characterize aquatic bio-degrading bacteria from the world’s largest lake, Khazar, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The length of fragments were approximately ≈ 1500 bp
Fig. 2 Neighbor-joining phylogenetic tree [ 26 ] derived from 16S rRNA gene sequence data [ 14 ] showing the positions of seven isolated bacteria including strains Khuz-1, Khuz-2 and Khuz-3 among related bacteria. Numbers at branch points are bootstrap percentages based on 500 replicates.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The length of fragments were approximately ≈ 1500 bp
Fig. 2 Neighbor-joining phylogenetic tree [ 26 ] derived from 16S rRNA gene sequence data [ 14 ] showing the positions of seven isolated bacteria including strains Khuz-1, Khuz-2 and Khuz-3 among related bacteria. Numbers at branch points are bootstrap percentages based on 500 replicates.
…”
Section: Resultsmentioning
confidence: 99%
“…Scientifics information on the safety and effectiveness of natural antibiotics’ remedies have shown that these agents have good anti-pathogenic activity with very low side effects [ 7 , 8 ]. The among microorganisms, environmental bacteria have various beneficial potations in medical and pharmaceutical applications such as bio-absorption of heavy metals [ 31 ], bio-remediation of toxics [ 14 ], production of antimicrobial peptides and antibiotics [ 32 34 ]. One of the most important methods for strain identification and distribution is 16S rRNA sequencing method [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, molecular approaches such as 16s rRNA gene sequencing are utilized as genetic markers for identifying the exact bacterial species and confirming the ancient methods (Ebrahimi et al 2020). In this study, after amplification and determination of the 16S rRNA gene sequence and comparing it in the NCBI GenBank database (https://www.ncbi.nlm.nih.gov/), the results showed that the isolate was closely related to the strains of E. coli, which confirmed our phenotypical findings (The GenBank accession number for the 16S rRNA gene isolate is OL798000).…”
Section: Phenotypic and Phylogenetic Identification Of The Isolatementioning
confidence: 99%